Paul's Concept of Salvation Theology and Its Relevance - Tarigan, Sayang; Simanjuntak, Ferry; Suwito, Tri Prapto (IJOSMAS, 2022)
- Salvation is available to all through the gospel (Rom. 1:16-17). The gospel contains God's saving act through the work of the Son of God who died, was crucified, buried, and rose again. For everyone who believes or believes in Jesus Christ the Son of God, it will obtain salvation through God's act of justification. This research provides a new understanding of the world of theology in general because it has broken the concepts of particular salvation, which are claimed by certain religions, specifically Judaism. The apostle Paul's view of salvation that can be obtained by all people without any distinction of ethnicity, culture, and religion has opened a new view of the way of salvation. Although the concept of salvation applies universally the people who are saved are only those who have been appointed to believe in Christ Jesus. The essence of the apostle Paul's teaching about salvation lies in the work of Jesus Christ, and the act of Salvation is done by none other than God Himself. Although the meaning of salvation for Paul has an inclusive element (for all who believe), the concept of salvation that he describes in Romans is exclusive. Because Paul uses his Jewish background and relates it to his understanding of God's saving act through the work of Jesus Christ. The term justification that Paul uses to describe salvation has a meaning if God as the Supreme Judge has saved people in the present and as a guarantee of salvation in the future.